HUBUNGAN KEKUATAN OTOT LENGAN TERHADAP HASIL TOLAK PLURU GAYA OBRAIN SISWA KELAS IX SMPN 03 SELUMA - Rosa, Elvina; Dewi, Citra; Apriansyah, Dolly (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
This study aims to determine the relationship between the strength of the arm muscles and the results of the obrain style shot put for class IX students of SMPN 3 SELUMA. This type of research is descriptive with correlational analysis by looking for relationships between variables and data collection techniques using tests and measurements with a population and sample of 12 students. The results of this study based on data analysis obtained a p-value (sig) 0.000 <0.05. Based on the results above, it can be concluded that there is a significant (significant) relationship between arm muscle strength and obrain-style bullet repulsion in class IX students of SMPN 3 SELUMA. Keywords: Relationship, Arm Muscle Strength, Shot Reject